2015
DOI: 10.1016/j.cell.2015.03.032
|View full text |Cite|
|
Sign up to set email alerts
|

Widespread Proteome Remodeling and Aggregation in Aging C. elegans

Abstract: SUMMARY Aging has been associated with a progressive decline of proteostasis, but how this process manifests itself at the level of proteome composition remains largely unexplored. Here we profiled more than 5,000 proteins along the lifespan of the nematode C. elegans. We find that one third of proteins change in abundance at least 2-fold during aging, resulting in a severe proteome imbalance. These changes are reduced in the long-lived daf-2 mutant, but enhanced in the short-lived daf-16 mutant. While ribosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

40
469
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 516 publications
(513 citation statements)
references
References 87 publications
40
469
4
Order By: Relevance
“…We now show that two other small HSP members that have activities on only one of the two substrates investigated here, one related to acute stress (CG14207) and one to chronic stress (HSP67Bc), also are capable of extending lifespan in Drosophila , demonstrating that increased levels of functionally diverse small HSPs can promote longevity in vivo by different protective activities that yet both contribute to an improved protein homeostasis. Notably, a recent extensive study on proteome remodeling and aggregation in aging C. elegans (Walther et al ., 2015) showed that among all chaperones, particularly small HSPs were associated with the increase in protein homeostasis in long‐lived daf‐2 mutant worms, consistent with the view that small HSPs play a pivotal role in the lifespan‐prolonging effect of the insulin/insulin‐like growth factor‐1 signaling pathway.…”
Section: Discussionsupporting
confidence: 70%
“…We now show that two other small HSP members that have activities on only one of the two substrates investigated here, one related to acute stress (CG14207) and one to chronic stress (HSP67Bc), also are capable of extending lifespan in Drosophila , demonstrating that increased levels of functionally diverse small HSPs can promote longevity in vivo by different protective activities that yet both contribute to an improved protein homeostasis. Notably, a recent extensive study on proteome remodeling and aggregation in aging C. elegans (Walther et al ., 2015) showed that among all chaperones, particularly small HSPs were associated with the increase in protein homeostasis in long‐lived daf‐2 mutant worms, consistent with the view that small HSPs play a pivotal role in the lifespan‐prolonging effect of the insulin/insulin‐like growth factor‐1 signaling pathway.…”
Section: Discussionsupporting
confidence: 70%
“…Importantly, evidence indicates that the amount of soluble, aggregate prone protein oligomers, rather than the abundance of pro tein aggregates, correlates with disease severity 23,24 . Therefore, protein aggregates, which contain both misfolded proteins and elevated levels of chaper ones, constitute an adequate PQC response, aimed at sequestering potentially harmful protein oligomers, rather than embodying the ultimate cellular threat 25 . This concept of aggregates as a form of cell protection might also apply to amyloid plaques, which are protein aggregates folded into fibrils to allow for many copies of the aberrant protein within a cell.…”
mentioning
confidence: 99%
“…To illustrate how the CNV approach can provide novel biological insights, we analyzed a time‐series mass spectrometry experiment related to aging of C. elegans (Walther et al , 2015). The abundance of proteins was calculated at five different time points during the lifespan of the organism (days 1, 6, 12, 17, and 22) using the SILAC approach (Ong et al , 2002).…”
Section: Resultsmentioning
confidence: 99%
“… Analysis of the abundance distribution for (A) cytoplasmic, (B) mitochondrial, and (C) extracellular proteins across five age groups in C. elegans (Walther et al , 2015). Each age group was compared against a pool reference sample using SILAC (Ong et al , 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation